Severe drug-induced liver injury in patients under treatment with antipsychotic drugs: Data from the AMSP study - Druschky, Katrin; Toto, Sermin; Bleich, Stefan; Baumgaertner, Jessica; Engel, Rolf R.; Grohmann, Renate; Maier, Hannah B.; Neyazi, Alexandra; Rudolph, Yannick J.; Ruether, Eckart; Schwoerer, Harald; Seifert, Johanna; et al. (World Journal of Biological Psychiatry, 2020)
Objectives Drug-induced liver injury (DILI) has been associated with various antipsychotic drugs (APDs). Comparative studies between individual APDs are largely not available. Methods Antipsychotic drug utilisation data and reports of severe antipsychotic DILI were assessed by using data from an observational pharmacovigilance programme-Arzneimittelsicherheit in der Psychiatrie (AMSP)-during the period 1993-2016. Results Of the 333,175 patients treated with APDs, a total of 246 (0.07%) events of severe DILI were identified. Phenothiazines were associated with significantly higher rates of severe DILI (0.03%, 95% CI = 0.02-0.04) than thioxanthenes (0.01%, 95% CI = 0.00-0.02) or butyrophenones (0.01%, 95% CI = 0.00-0.01). Among individual drugs, olanzapine (0.12%, 95% CI = 0.10-0.16), perazine (0.09%, 95% CI = 0.05-0.15) and clozapine (0.09%, 95% CI = 0.10-0.12 ranked highest. In 78 cases (31.7%), combination therapies with antipsychotic and antidepressant drugs or with two or more APDs were considered responsible. Male sex and a diagnosis of mania were associated with significantly higher rates of severe DILI while older patients (>= 65 years old) were significantly less often affected. Conclusions In the present analysis of a representative psychiatric inpatient cohort, olanzapine, perazine, and clozapine were the most common individual APDs associated with severe DILI.
CRIS-Team WoS Importer:2020-10-09